Praktik Akuntansi Pada Upacara Adat Li Mati Li Heda Dengan Menggunakan Pendekatan Etnografi - Jetofandri Umbu Neka Dapamoni; Ana Sopanah; Khojanah Hasan (Politeknik Ganesha Medan, 2025)
This study is based on the traditional death ceremony Li Mati Li Heda in Anakalang, Central Sumba, which, beyond its cultural and spiritual significance, also involves resource management practices resembling accounting. The purpose of this research is to reveal the values of local wisdom, measurement standards, and recording practices embedded in the ceremony. A qualitative approach with an ethnographic method was applied, utilizing participatory observation, in-depth interviews, and documentation, while data validity was ensured through triangulation and member checks. The results indicate five core values of local wisdom, namely respect for ancestors, social solidarity, adherence to tradition, cultural identity, and spirituality; in addition, resource measurement was conducted using customary standards, and systematic records of revenues and expenditures were maintained by designated community members. In conclusion, the Li Mati Li Heda ceremony demonstrates that accounting practices can emerge from local traditions, functioning as a form of social accountability, ensuring transparency, and reinforcing cultural identity within the community. This study contributes to the literature on cultural accounting by showing how systematic recording and accountability practices are embedded in local traditions, beyond symbolic or social obligations found in similar ceremonies.